2016
DOI: 10.1111/apt.13554
|View full text |Cite
|
Sign up to set email alerts
|

Years of life that could be saved from prevention of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma occurrence results in the loss of a considerable number of years-of-life, especially for younger patients. In recent years, the increased possibility of effectively treating this tumour has improved life expectancy, thus reducing years-of-life lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The curve of logit transformation of the relative survival between the index cohort and the reference population would follow an approximately straight line if the excess hazard of the patients remains constant over time (Fang, Chang, Hsu, et al, ). This method has been successfully validated with simulation data and has been used to analyze real data in several studies (e.g., Cucchetti, Trevisani, Bucci, et al, , Hung et al, , , H. Y. Lee et al, , Yang, Lee, Hsu, et al, ; Yang, Lai, Chang, et al, ). The assumption of an excess constant hazard, however, is usually untestable with a limited observed time period, because how closely the curve of logit‐transformed relative survival approaches a straight line is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The curve of logit transformation of the relative survival between the index cohort and the reference population would follow an approximately straight line if the excess hazard of the patients remains constant over time (Fang, Chang, Hsu, et al, ). This method has been successfully validated with simulation data and has been used to analyze real data in several studies (e.g., Cucchetti, Trevisani, Bucci, et al, , Hung et al, , , H. Y. Lee et al, , Yang, Lee, Hsu, et al, ; Yang, Lai, Chang, et al, ). The assumption of an excess constant hazard, however, is usually untestable with a limited observed time period, because how closely the curve of logit‐transformed relative survival approaches a straight line is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…To view this article visit https://doi.org/10.1111/apt.13813. DEAR SIR, We read with interest the recent study by Cole et al 1 In the article, proton pump inhibitors (PPIs) prescription was associated with severity of cirrhosis, even though no significant relationship between PPIs and mortality was observed. 1 Safety of PPIs in patients with cirrhosis has been recently questioned as studies revealed association between these drugs not only with spontaneous bacterial peritonitis but also with worse prognosis.…”
Section: Linked Contentmentioning
confidence: 99%
“…1 Clinical response and remission rates were 61% and 24% in Crohn's disease and 57% and 24% in ulcerative colitis, respectively, after fourteen weeks of VDZ treatment. The three most common adverse events were joint pain, acne and nasopharyngitis.…”
mentioning
confidence: 93%
“…Notably, there is a decrease of infection-related cases but an increase in cases related to other risk factors, with NASH being the predominant factor [3]. For younger patients, HCC results in the loss of a considerable number of years-of-life with an estimated lifespan loss of 19.1 years shown in a recent study [4]. The knowledge about risk factors for HCC provides the opportunity and chance for the development and implementation of preventative strategies aiming at an efficient and effective prevention of HCC to decrease the worldwide burden of the disease [5].…”
Section: Introductionmentioning
confidence: 99%